2015
DOI: 10.6018/analesps.32.1.216221
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades fonológicas suprasegmentales y desarrollo lector en niños de educación primaria

Abstract: Resumen: En la última década diversos estudios han demostrado que las habilidades fonológicas suprasegmentales o prosódicas (conocimiento de los rasgos prosódicos del lenguaje tales como el acento, las pausas y la entonación) influyen en el desarrollo de la lectoescritura. Sin embargo, la mayoría de los estudios se han realizado en inglés y se han centrado fundamentalmente en el análisis de las habilidades suprasegmentales a nivel léxi-co. Este estudio analiza las relaciones entre las habilidades suprasegmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
6
0
8
Order By: Relevance
“…Research across languages shows that children follow the same progression of development of PA: sensitivity to syllables develops first followed by onsets and rimes and finally, phonemes (e.g., Villalón, 2008;Anthony, Williams, Durán & Laing, 2011;Gutiérrez, et al, 2020). In Spanish, along with phoneme awareness, syllable awareness plays a significant role in reading (Herrera & Defior, 2005;Anthony et al, 2011;Calet, Flores, Jiménez-Fernández & Defior, 2016). However, by kindergarten, the majority of Spanish-speaking children seem to have mastered syllable awareness (Defior & Herrera, 2003;Herrera et al, 2007;De la Calle, Aguilar & Navarro, 2016).…”
Section: Pa and Literacy Developmentmentioning
confidence: 99%
“…Research across languages shows that children follow the same progression of development of PA: sensitivity to syllables develops first followed by onsets and rimes and finally, phonemes (e.g., Villalón, 2008;Anthony, Williams, Durán & Laing, 2011;Gutiérrez, et al, 2020). In Spanish, along with phoneme awareness, syllable awareness plays a significant role in reading (Herrera & Defior, 2005;Anthony et al, 2011;Calet, Flores, Jiménez-Fernández & Defior, 2016). However, by kindergarten, the majority of Spanish-speaking children seem to have mastered syllable awareness (Defior & Herrera, 2003;Herrera et al, 2007;De la Calle, Aguilar & Navarro, 2016).…”
Section: Pa and Literacy Developmentmentioning
confidence: 99%
“…Unlike the accuracy and speed of reading in dyslexics, suprasegmental phonology or prosody is the element of fluency that has received the least attention. This gap widens when comparing studies conducted in English (Calet et al, 2016) with studies conducted in transparent languages such as Spanish. Two studies carried out with Spanish dyslexic people inform that they have differences compared to typical readers regarding prosody performance (Suárez-Coalla et al, 2016;Jimenez-Fernandez et al, 2015).…”
Section: Fluency Dyslexia and Prosody In The Spanish Languagementioning
confidence: 99%
“…Different studies have shown that prosody is related to the acquisition and development of various written language skills such as reading words (Whalley & Hansen, 2006), the reading of words and pseudowords , achieving fluent reading (Schwanenflugel et al, 2004) and reading comprehension (Calet et al, 2016;Kanik Uysal & Bilge, 2018;Miller & Schwanenflugel, 2006Whalley & Hansen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…En la educación parvularia, los niños poseen modelos gráficos que constituyen una condición fundamental para la representación gráfica de los objetos; además, a esa edad inician en la construcción de objetos determinados que se les entregan en calidad de modelo (Calet et al 2016). Al final de la edad preescolar, el niño utiliza modelos esquemáticos, logro en el desarrollo del pensamiento infantil que permite establecer relaciones entre los objetos, hechos y fenómenos del medio, lo que puede considerarse como etapa propedéutica para el desarrollo de esta habilidad en los subsiguientes grados académicos.…”
Section: Taxonomías De Las Habilidades Intelectuales Generalesunclassified